State and regime capacity in authoritarian elections: Egypt before the Arab spring. Issue 1 (January 2018) - Koehler, Kevin
Scholarship on electoral authoritarianism has increasingly recognized state capacity as an element enhancing electoral control. Building on such arguments, I examine the interaction between state capacity and regime strength in authoritarian elections. Drawing on empirical evidence from Egyptian elections under Mubarak, I show that the degree to which official regime candidates were able to profit from state penetration depended on the strength of the ruling party. In urban settings where party structures were stronger, service provision by the state helped secure the dominance of the hegemonic National Democratic Party; in rural constituencies where the party was weak, by contrast, service provision strengthened local elites who often ran and won against the party's official candidates. This suggests that variation in regime capacity to channel political support needs to be taken into account when examining the relationship between state capacity and electoral control under authoritarianism.